2020
DOI: 10.1177/0846537119888390
|View full text |Cite
|
Sign up to set email alerts
|

Use of Multiphase CT Protocols in 18 Countries: Appropriateness and Radiation Doses

Abstract: Purpose: To assess the frequency, appropriateness, and radiation doses associated with multiphase computed tomography (CT) protocols for routine chest and abdomen–pelvis examinations in 18 countries. Materials and Methods: In collaboration with the International Atomic Energy Agency, multi-institutional data on clinical indications, number of scan phases, scan parameters, and radiation dose descriptors (CT dose–index volume; dose–length product [DLP]) were collected for routine chest (n = 1706 patients) and ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 15 publications
(56 reference statements)
2
10
0
Order By: Relevance
“…It must be noted that multi-phase CT examinations, especially in routine chest CT, are reported to be unnecessary for most clinical indications. From the study of data on clinical indications recorded for multi-phase CT collected for 1706 patients from 11 institutions in 18 countries, other authors found that 100% of routine chest CT and 63% of routine abdomen-pelvis CT examinations were unnecessary ( 2 ). Karla et al noted that most publications on chest CT in COVID-19 pneumonia without complication report a single-phase, non-contrast chest CT and there is little use of contrast CT images from multi-phase scans because the clinical findings in COVID-19 pneumonia are mostly restricted to lungs ( 3 ).…”
mentioning
confidence: 99%
“…It must be noted that multi-phase CT examinations, especially in routine chest CT, are reported to be unnecessary for most clinical indications. From the study of data on clinical indications recorded for multi-phase CT collected for 1706 patients from 11 institutions in 18 countries, other authors found that 100% of routine chest CT and 63% of routine abdomen-pelvis CT examinations were unnecessary ( 2 ). Karla et al noted that most publications on chest CT in COVID-19 pneumonia without complication report a single-phase, non-contrast chest CT and there is little use of contrast CT images from multi-phase scans because the clinical findings in COVID-19 pneumonia are mostly restricted to lungs ( 3 ).…”
mentioning
confidence: 99%
“…Even with the same clinical indication, large body habitus, or longer scan length of a clinically indicated body region can increase radiation dose. Another factor linked to clinical indications is imaging with multiple scan phases or for lesions that require better spatial resolution, both of which can compromise the extent to which radiation dose can be reduced [9,[29][30][31][32].…”
Section: Ct Radiation Risks and Optimizationmentioning
confidence: 99%
“…Per exam, dose in CT has varied from about a mSv to about 15 mSv. Recent studies have shown that with the use of multiphase CT imaging and recurrent imaging, much higher doses are being received by some patients [11,12], as discussed later. Also, the use of CT for performing interventions has led to as much as 100 mSv in a single procedure [13].…”
Section: Introductionmentioning
confidence: 96%